Cellular sex throughout the organism underlies somatic sexual differentiation. - Hérault, C.; Pihl, T.; Hudry, B. (Nature communications, 2024)
Sex chromosomes underlie the development of male or female sex organs across species. While systemic signals derived from sex organs prominently contribute to sex-linked differences, it is unclear whether the intrinsic presence of sex chromosomes in somatic tissues has a specific function. Here, we use genetic tools to show that cellular sex is crucial for sexual differentiation throughout the body in Drosophila melanogaster. We reveal that every somatic cell converts the intrinsic presence of sex chromosomes into the active production of a sex determinant, a female specific serine- and arginine-rich (SR) splicing factor. This discovery dismisses the mosaic model which posits that only a subset of cells has the potential to sexually differentiate. Using cell-specific sex reversals, we show that this prevalence of cellular sex drives sex differences in organ size and body weight and is essential for fecundity. These findings demonstrate that cellular sex drives differentiation programs at an organismal scale and highlight the importance of cellular sex pathways in sex trait evolution.